Dynamics of New Building Construction Costs: Implications for Forecasting Escalation Allowances. Issue 3 (1st September 2016) - Dugan, Michael T.; Ewing, Bradley T.; Thompson, Mark A.
Abstract : Construction projects often require multiple years to complete and the costs of supplies, materials, and labor may increase substantially during a project's time span. As a result, construction contracts often include an escalation clause to account for cost increases. This article examines the time-series properties of new building construction costs using several producer price indexes. Using a battery of unit root tests, we find substantial evidence that construction cost indexes are generally nonstationary. This finding has implications for the proper specification and use of these series in contract escalation clauses and their respective use in forecasting construction cost increases.